Study of Some Aspects of Egg Laying Behaviors of Fresh Water Teleostean Fish Mastacembelus Armatus (LAC): An investigation into the egg laying behaviors and feeding habits of the freshwater teleostean fish Mastacembelus Armatus (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Spiny Eel is an economically important teleostean freshwater species. Because of its delicious flavor and good nutritional value, it is a famous table fish. Monthly fish samples from the NCR area were collected between January and December 2016. Male displays a small dominance over female figures. The carnivorous and active predatory habits of M. armatus indicated a well-formed toothpaste, absence of gill rakers, a firmly constructed stomach and small intestines along with the prevalence of animal matter inside gut material. Body width was roughly of total body weight, resulting in a slim body across all life stages of M. armatus. This also suggested an aggressive mobile lifestyle that is ideal for its predatory existence. Fish are raised on types of food materials, for example. Fish, marine insects and muds collected as 16.60, 14.75, 10.78, 8.50, 8.28 and 13.52 percent in average, respectively. 80.94 of the fish displayed aggressive feeding during the time.